The Impact of Simultaneous Liver Resection for Occult Liver Metastases of Pancreatic Adenocarcinoma - F. Klein; G. Puhl; O. Guckelberger; U. Pelzer; J. R. Pullankavumkal; S. Guel; P. Neuhaus; M. Bahra (Gastroenterology Research and Practice)
Backround. Pancreas resection is the only curative treatment for pancreatic adenocarcinoma. In the event of unexpected incidental liver metastases during operative exploration patients were traditionally referred to palliative treatment arms. With continuous progress in the surgical expertise simultaneous pancreas and liver resections seem technically feasible nowadays. The aim of this study therefore was to analyze the impact of synchronous liver-directed therapy on operative outcome and overall survival in patients with hepatic metastasized pancreatic adenocarcinoma (HMPA). Methods. 22 patients who underwent simultaneous pancreas resection and liver-directed therapy for HMPA between January 1, 2004 and January 1, 2009 were compared to 22 patients who underwent classic pancreas resection for nonmetastasized pancreatic adenocarcinoma (NMPA) in a matched pair study design. Postoperative morbidity, preoperative, and operative data and overall survival were analyzed. Results. Overall survival was significantly decreased in the HMPA group. Postoperative morbidity and mortality and median operation time did not significantly differ between the groups. Conclusion. The results of our study showed that simultaneous pancreas resection and liver-directed therapy may safely be performed and may therefore be applied in individual patients with HMPA. However, a potential benefit of this radical surgical approach with regard to overall survival and/or quality of life remains to be proven.